2017
DOI: 10.1016/j.ajo.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intraocular Pressure With Human Immunodeficiency Virus

Abstract: Absolute CD4 counts may play a role in IOP fluctuations. This association was found in patients with HIV regardless of whether patients were on HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
2
2
2
Order By: Relevance
“…Indeed, decreased cone-photoreceptor density in HIV+ participants was found using an adaptive optics camera [59] and SD-OCT visualized possible changes in retinal layers other than GCL and RNFL [5,60,61]. Lower IOP in HIV+ participants was previously described and its causes are more likely multifactorial [61]. Our results showed that this diminished IOP persists in PLHIVs with long-term, well-sustained immune control.…”
Section: Plos Onesupporting
confidence: 65%
See 1 more Smart Citation
“…Indeed, decreased cone-photoreceptor density in HIV+ participants was found using an adaptive optics camera [59] and SD-OCT visualized possible changes in retinal layers other than GCL and RNFL [5,60,61]. Lower IOP in HIV+ participants was previously described and its causes are more likely multifactorial [61]. Our results showed that this diminished IOP persists in PLHIVs with long-term, well-sustained immune control.…”
Section: Plos Onesupporting
confidence: 65%
“…That decline could however be explained by functional changes without structural damage of the retinal ganglion cells or other cells implicated in vision. Indeed, decreased cone-photoreceptor density in HIV+ participants was found using an adaptive optics camera [59] and SD-OCT visualized possible changes in retinal layers other than GCL and RNFL [5,60,61]. Lower IOP in HIV+ participants was previously described and its causes are more likely multifactorial [61].…”
Section: Plos Onementioning
confidence: 84%
“…No relevance to demographic data was reported in any other study reviewed,7,813 but it was observed in this study that age was a factor with statistical relevance for IOP decrease. It is also added that in the analysis of patients with HIV without treatment was the group with the lowest mean age.…”
Section: Discussioncontrasting
confidence: 70%
“…Recently, IOP was compared in patients with HIV under treatment and without treatment with the control group. The results were promising in knowing that the IOP of HIV patients was lower than the control, and there was a direct relationship with the amount of TCD4 in the patients, where HIV patients were 7 times more likely to have a decrease of IOP and if the TCD4 count was <700 cells/mm 3 there is 13 times greater chance of having a reduction in IOP 7. This study obtained the same pattern of patient division.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation